The Management of Traumatic Optic Neuropathy: A Systematic Review and Meta-Analysis - Fallahzadeh, Mohammad; Amirreza Veisi; Faezeh Tajari; Zahra Khorrami; Mehri Farhang Ranjbar; Roozbeh Tavanaei; Ghassembaglou, Navid; Seyed Hadi Aghili (Archives of Academic Emergency Medicine, 2024)
Introduction: Traumatic optic neuropathy (TON) is a serious condition resulting from optic nerve injury, often due to head trauma. This study systematically reviews the existing literature to evaluate the effectiveness of various treatments in improving visual outcomes in TON patients. Methods: A comprehensive literature search was conducted across databases including Medline (via PubMed), Web of Science, Cochrane Library, and EMBASE from January 1992 to October 2024. Studies were selected based on inclusion criteria that focused on TON patients treated with corticosteroids, conservative therapy, erythropoietin therapy, or surgical interventions. Quality assessment of the included studies was performed using the Joanna Briggs Institute (JBI) Risk of Bias Tool for each design. Data extraction and quality assessment were performed by two independent reviewers, with a meta-analysis conducted to evaluate the pooled visual acuity (VA) improvement rates. Results: A total of 23 studies were included, encompassing 1,851 patients with TON. The meta-analysis revealed a pooled VA improvement rate of 50.6% across all treatment modalities. Specifically, corticosteroid-only treatment resulted in a 56.2% improvement rate, while combined corticosteroid and surgical decompression showed a 42.9% improvement rate. Conservative therapy had a 47.8% improvement rate. The heterogeneity among studies was significant (I2= 89.9%), and no significant publication bias was detected. Subgroup analyses indicated varied outcomes, with some studies reporting better results with early intervention. Conclusion: The treatment of TON remains challenging, with no single modality showing clear superiority. The corticosteroids and surgical interventions provide potential benefits; however, conservative therapy might be appropriate for certain cases. Future research should focus on optimizing treatment protocols and exploring new therapeutic options, such as erythropoietin to improve visual outcomes in TON patients.